IMPLEMENTATION OF SAVINGS PRODUCTS IN MUDHARABAH AGREEMENTS ACCORDING TO MUAMALAH FIQH AT BMT NU KALIBARU BRANCH - Karyono (International Journal of Multidisciplinary Reseach, 2025)
The purpose of this study is to analyze and evaluate the implementation of mudharabah savings products at BMT NU Kalibaru Branch based on the perspective of fiqih muamalah. This study uses a qualitative case study approach to analyze the implementation of mudharabah savings at BMT NU Kalibaru Branch based on fiqih muamalah. Data was collected through in-depth interviews, participatory observation, and documentation. The research subjects included managers, staff, and customers. Data analysis used the Miles and Huberman model (reduction, presentation, verification), with triangulation of sources and techniques to test validity. The focus of the study includes the clarity of the contract, the fairness of the profit-sharing ratio, transparency, and accountability, to provide a comprehensive overview and practical recommendations for the management of BMT. The results of this study indicate that the implementation of mudharabah savings at BMT NU Branch Kalibaru has adhered to the principles of Islamic jurisprudence through the agreement on the profit-sharing ratio and the implementation of Sharia principles. However, the practice is not yet optimal. Customers' Islamic financial literacy remains low, with some perceiving the profit-sharing system as similar to bank interest. Contract documentation, especially for small deposits, is often conducted orally without written evidence, reducing legal clarity. Transparency in profit calculations and reporting is also minimal. Regular education, written contract documentation for all customers, and simple yet informative reporting of business results are needed to ensure that Sharia principles are implemented substantively, not merely as a symbol.